Response Reaction of Deschampsia Antarctica desv. Plants to UV-B Irradiation and Oxidative Stress - Taran, N.Yu.; Okanenko, A.A.; Batsmanova, L.M.; Svetlova, N.B. (Український антарктичний журнал, 2009)
The effect of stress factors – ultraviolet radiation (UV-B) and hydrogen peroxide (H₂O₂) upon two species of Deschampsia plants – D. antarctica and D. caespitosa were studied. Investigations performed with D. Antarctica plant samples delivered of Antarctic and D. caespitosa from Carpathian Mountains showed that UV-B radiation caused changes mainly pigment composition - chlorophyll a and almost all (except violaxanthin) carotenoids. Lipid composition was characterized by accumulation of triacylglicerols, sulphoquinovosyl diacylglycerol and phopsphatydylcholine while monogalacto-syldiacylglycerol quantity decreased. H₂O₂ treatment cause increase chlorophyll a content in both species and carotenoids in D. antarctica plants. Concerning glycolipid composition one could see monogalactosyldiacylglycerol content decrease in D. caespitosa whereas only insignificant SQDG enlargement was noted in D. antarctica leaves. Досліджувався вплив стресових факторів – ультрафіолетового випромінювання (UV-B) та пероксиду водню (H₂O₂) на представників двох видів роду Deschampsia – D. аntarctica і D. caespitosa. Встановлено, що UV-B випромінюванняя викликало зміни у вмісті пігментів – хлорофілів і каротиноїдів (крім віолоксантину) Склад ліпідів характеризувся накопиченням триацилгліцеролів, сульфохіновадилдіацилгліцеролу, фосфатидилхоліну та деструкцією вмісту моногалактозилдіацилгліцеролу. Вплив H₂O₂ спричиняв акумуляцію вмісту хлорофілу а в рослинах обох видів і каротиноїдів у рослинах D . antarctica. Дослідження в місту гліколіпідів встановило зменшення вмісту моногалактозилдіацилгліцеролу в листках D. caespitosa та незначне накопичення сульфохіновадилдіацилгліцеролу в рослинах D. antarctica. Исследовалось влияние стрессовых факторов – ультрафиолетового излучения (UV-B) и перекиси водорода (H₂O₂) на представителей двух видов рода Deschampsia – D. аntarctica и D. caespitosa. Установлено, что UV-B излучение вызвало изменения в содержании пигментов – хлорофиллов и каротиноидов (кроме виолоксантина). Состав липидов характеризовался накоплением триацилглицеролов, сульфохиновазилдиацилглицерола, фосфатидилхолина и деструкцией содержания моногалактозил-диацилглицерола. Влияние H O вызывало аккумуляцию содержания хлорофилла a в2 2 растениях обоих видов и каротиноидов в растениях D. antarctica. Исследование состава гликолипидов установило уменьшение содержания моногалактозилдиацилглицерола в листьях D. caespitosa и незначительное накопление сульфохиновадилдиацилглицерола в растениях D. Antarctica.